Phenol-soluble modulins: novel virulence-associated peptides of staphylococci. (February 2014) - Li, Shu; Huang, Hui; Rao, Xiancai; Chen, Wei; Wang, Zhengqing; Hu, Xiaomei
ABSTRACT: Phenol-soluble modulins (PSMs), a novel class of small peptides with an amphipathic α-helical structure and strong surfactant-like properties, are produced by most staphylococci, especially pathogenic Staphylococcus aureus and Staphylococcus epidermidis . PSMs can: induce the production of proinflammatory cytokines; recruit, activate and lyse neutrophils to help staphylococci evade immune damage; lyse erythrocytes and are associated with the hemolysis of staphylococcal disease; facilitate the structuring and detachment of staphylococcal biofilms and disseminate biofilm-associated infection; and kill competing microbes and act as weapons in interbacterial warfare. Therefore, PSMs are considered to be critical virulence-associated factors and to play important roles in the pathogenesis of staphylococci. This review summarizes the classification, structure, expression regulation and biological functions of PSMs. The possible means to prevent PSM-associated diseases are also outlined in order to emphasize the need to investigate PSMs as potential targets for drug and vaccine design against staphylococcal infections.